Analisis Tingkat Pengetahuan, Sikap Keuangan Pribadi dan Perilaku Keuangan Pribadi Mahasiswa Jurusan Akuntansi Politeknik Negeri Malang - Syuliswati, Atika; Asdani, Andi (Akutansi Bisnis & Manajemen ( ABM ), 2018)
Many students still don’t understand how to invest or to access the capital markets and money markets, because students don’t have enough knowledge about it. Meanwhile, education about personal finance remains as a major challenge in Indonesia. The purpose of this study was to analize of Personal Financial Knowledge, personal finance attitudes, personal finance behavior for 4th year and senior students Accounting Department at State Polytechnic Of Malang. The population in this study were students from Accounting Department at State Polytechnic Of Malang, for 4th year and senior students. Data in the form are primary data and sample were spread as much as 120 for 4th and 89 for 8th semester students (n = 209). The method that used is descriptive statistics, validity test, reliability test and t-test. Personal financial knowledge and personal behavior finance were significant differences between 4th and 8th semester students. For personal financial knowledge with significant value 0.000, and personal finance behavior with significant value 0.000. Personal financial attitudes was not significant differences between 4th and 8th semester students. For personal finance attitudes with significant value 0.064.